2008
DOI: 10.1007/s11999-008-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Hip Contact Stress Predicts Osteoarthritis in DDH

Abstract: Hip stresses are generally believed to influence whether a hip develops osteoarthritis (OA); similarly, various osteotomies have been proposed to reduce contact stresses and the risk of OA. We asked whether elevated hip contact stress predicted osteoarthritis in initially asymptomatic human hips. We identified 58 nonoperatively treated nonsubluxated hips with developmental dysplasia (DDH) without symptoms at skeletal maturity; the control group included 48 adult hips without hip disease. The minimum followup w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Previous mathematical and FE studies have assumed spherical, concentric geometry [14, 42, 43], and have mostly omitted the acetabular labrum [42, 43]. By simple description of stress as force divided by area, it would follow that any global reduction in coverage would cause an increase in cartilage contact stress for idealized hip geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mathematical and FE studies have assumed spherical, concentric geometry [14, 42, 43], and have mostly omitted the acetabular labrum [42, 43]. By simple description of stress as force divided by area, it would follow that any global reduction in coverage would cause an increase in cartilage contact stress for idealized hip geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DDH present with morphologic abnormalities, such as insufficient acetabular coverage of the femoral head, a shallow acetabular concavity, and a maloriented acetabulum [6,14,26]. These deformities lead to abnormal stress distributions on the articular weightbearing area, elevated joint contact pressures, and shearing stresses on the acetabular rim complex [10,12,24]. Thus, these patients often have labral tearing and cartilage degeneration develop at an early age, resulting in premature hip osteoarthritis [18,26,30,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical evaluation of hip joint after Salter innominate osteotomy: a long-term follow-up study. Arch Orthop Trauma Surg, 121, (511-516), ISSN 0936-8051 Zupanc, O., Križančič, M., Daniel, M., Mavčič, B., Antolič, V., Iglič, A., Kralj-Iglič, V., (2008).…”
Section: Acknowledgementmentioning
confidence: 99%
“…In particular, the results indicated that long lasting elevated contact stress is connected to degeneration of the hip articular cartilage and development of hip osteoarthritis (Dolinar (2003); Kralj (2005); 2008); Pompe (2003); Rečnik (2007;2009a;). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation